Simplify by combining like terms 2/8x+3/10y-5/8x+4/10y

1 answer

To simplify the expression 2/8x + 3/10y - 5/8x + 4/10y, we can combine the terms with the same variables.

First, let's combine the terms with the x variable:
2/8x - 5/8x = (2 - 5)/8x = -3/8x

Next, let's combine the terms with the y variable:
3/10y + 4/10y = (3 + 4)/10y = 7/10y

Putting it all together, we have:
-3/8x + 7/10y

The simplified form of the expression is -3/8x + 7/10y.
Similar Questions
    1. answers icon 4 answers
    1. answers icon 1 answer
  1. Simplify the expression by combining any like terms.4y+6-2y-9=_____ (Simplify your answer. Do not​ factor.)
    1. answers icon 1 answer
  2. Simplify the algebraic expression by combining like terms.(Simplify your​ answer.) -5x^2+13x^2=
    1. answers icon 1 answer
more similar questions